The Principle of the Indiscernibility of Identicals Requires No Restrictions - Maunu Ari (Springer, 2022)
There is a certain argument against the principle of the indiscernibility of identicals (PInI), or the thesis that whatever is true of a thing is true of anything identical with that thing. In this argument, PInI is used together with the self-evident principle of the necessity of self-identity ("necessarily, a thing is identical with itself") to reach the conclusion a=b → □a=b, which is held to be paradoxical and, thus, fatal to PInI (in its universal, unrestricted form). My purpose is to show that the argument in question does not have this consequence. Further, I argue that PInI is a universally valid principle which can be used to prove the necessity of identity (which in fact is how the argument in question is usually employed).